Labeling amine-modified DNA with a novel amine-reactive coumarin: An efficient alternative for synthesizing singly fluorescent-labeled FISH probes. - González-Pérez, Marina (2017)
The suitability of using a novel coumarin TFP ester for the synthesis of fluorescent FISH probes with a single fluorophore was investigated in this work.